America and the Japanese miracle : the Cold War context of Japan's postwar economic revival, 1950-1960 - Forsberg, Aaron (Luther Hartwell Hodges series on business, society, and the state., 2000)
"In America and the Japanese Miracle. Aaron Forsberg presents an account of Japan's postwar economic resurgence in a world polarized by the Cold War. His interpretation brings to light the many connections between Japan's economic revival and changes that occurred in the wider world during the 1950s."--Jacket